Stosunek religii do nauki. Punkt widzenia prawosławnego - Henryk Paprocki (Polonia Sacra)
Polish astronomer Konrad Rudnicki suggested that the so-called Copernican revolution, with far-reaching consequences for western Christianity, was hardly noticed in orthodoxy. In this case, the domain of discoveries and scientific truths remained distinct from the strictly theological domain. The Earth was treated as a mystical centre of the universe because of the Incarnation of Christ, which did not mean that it was also the real centre of the empirical universe. However, Copernicus’s discovery led to a rapidly progressive process of the western Church distancing itself from science. On the other hand, discoveries and scientific theories can in no case be contrary to the principles of faith, because we are dealing here with two different cognitive methods. It is the point of destination of both methods that should be the same.